Influences of source conditions on mountain wave penetration into the stratosphere and mesosphere. Issue 21 (6th November 2015) - Kaifler, Bernd; Kaifler, Natalie; Ehard, Benedikt; Dörnbrack, Andreas; Rapp, Markus; Fritts, David C.
Abstract: We present atmospheric gravity wave (GW) measurements obtained by a Rayleigh/Raman lidar at Lauder, New Zealand, (45°S, 170°E) during and after the Deep Propagating Gravity Wave Experiment campaign. GW activity and characteristics are derived from 557 h of high‐resolution lidar data recorded between June and November 2014 in an altitude range between 28 and 76 km. In this period, strong GW activity occurred in sporadic intervals lasting a few days. Enhanced stratospheric GW potential energy density is detected during periods with high tropospheric wind speeds perpendicular to New Zealand's Southern Alps. These enhancements are associated with the occurrence of quasi‐stationary GW (mountain waves). Surprisingly, the largest response in the mesosphere is observed for conditions with low to moderate lower tropospheric wind speeds (2–12 m/s). On the other hand, large‐amplitude mountain waves excited by strong tropospheric forcings often do not reach mesospheric altitudes, either due to wave breaking and dissipation in the stratosphere or refraction away from New Zealand. Key Points: Deep propagation of mountain waves occurs under conditions of weak to moderate forcing Large‐amplitude waves often break in the stratosphere or are refracted away from New Zealand Sufficiently strong stratospheric winds allow propagation of mountain waves to mesospheric altitudes